Determining site occupancy of acetaminophen covalent binding to target proteins in vitro. Issue 5 (24th March 2021) - Geib, Timon; Lento, Cristina; Marensi, Vanessa; Thulasingam, Madhuranayaki; Haeggström, Jesper Z.; Olsson, Magnus; Wilson, Derek J.; Leslie, Elaine M.; Sleno, Lekha
Abstract: Acetaminophen (APAP)‐related toxicity is caused by the formation of N ‐acetyl p ‐benzoquinone imine (NAPQI), a reactive metabolite able to covalently bind to protein thiols. A targeted liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method, using multiple reaction monitoring (MRM), was developed to measure APAP binding on selected target proteins, including glutathione S ‐transferases (GSTs). In vitro incubations with CYP3A4 were performed to form APAP in the presence of different proteins, including four purified GST isozymes. A custom alkylation agent was used to prepare heavy labeled modified protein containing a structural isomer of APAP on all cysteine residues for isotope dilution. APAP incubations were spiked with heavy labeled protein, digested with either trypsin or pepsin, followed by peptide fractionation by HPLC prior to LC‐MRM analysis. Relative site occupancy on the protein‐level was used for comparing levels of modification of different sites in target proteins, after validation of protein and peptide‐level relative quantitation using human serum albumin as a model system. In total, seven modification sites were quantified, namely Cys115 and 174 in GSTM2, Cys15, 48 and 170 in GSTP1, and Cys50 in human MGST1 and rat MGST1. In addition, APAP site occupancies of three proteins from liver microsomes were also quantified by using heavily labeled microsomes spiked into APAP microsomal incubations. A novel approach employing an isotope‐labeled alkylation reagent was used to determine site occupancies on multiple protein thiols.